2014
DOI: 10.1371/journal.pone.0098863
|View full text |Cite
|
Sign up to set email alerts
|

Large Conductance Ca2+-Activated K+ Channel (BKCa) α-Subunit Splice Variants in Resistance Arteries from Rat Cerebral and Skeletal Muscle Vasculature

Abstract: Previous studies report functional differences in large conductance Ca2+ activated-K+ channels (BKCa) of smooth muscle cells (VSMC) from rat cerebral and cremaster muscle resistance arteries. The present studies aimed to determine if this complexity in BKCa activity may, in part, be due to splice variants in the pore-forming α-subunit. BKCa variants in the intracellular C terminus of the α-subunit, and their relative expression to total α-subunit, were examined by qPCR. Sequencing of RT-PCR products showed two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…As described previously (Nourian et al . ; Lee et al . ), total RNA was extracted from 1A arterioles using the Arcturus PicoPure RNA isolation kit (Applied Biosystems, Carlsbad, CA, USA) and on‐column DNase I (Qiagen, Valencia, CA, USA) to minimize contamination from genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously (Nourian et al . ; Lee et al . ), total RNA was extracted from 1A arterioles using the Arcturus PicoPure RNA isolation kit (Applied Biosystems, Carlsbad, CA, USA) and on‐column DNase I (Qiagen, Valencia, CA, USA) to minimize contamination from genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Put in more physiological terms, the high Ca 2+ setpoint in cremasteric arteriolar muscle cells means that the internal face of the membrane of these cells must be exposed to Ca 2+ concentrations on the order of 3 µM for any activity of the channels to be observed at negative membrane potentials (665, 672). A high Ca 2+ setpoint (~12 µmol/L) has also been measured in SMCs isolated from rat first-order cremaster arterioles (1593), and appears to arise from reduced expression of β1 subunits in these arteriolar SMCs relative to cerebral arteries (1589, 1593) and possible differences in expression of spliced variants (1098). It was also shown that siRNA knockdown of β1 subunit expression in SMCs isolated from cerebral arteries produced a phenotype (increased Ca 2+ setpoint) similar to what was observed in cremaster arteriolar SMCs (1593).…”
Section: Bkca Channelsmentioning
confidence: 98%
“…In contrast to cerebral resistance arteries, some other arteries do not display this tight spark-STOC coupling. In particular, arteries supplying skeletal muscle have BK Ca channels that have lower Ca 2+ sensitivity and that are not activated by sparks, and this is thought to be due to lower expression of the β 1 subunit relative to the α subunit as well as a lower overall level of α -subunit expression ( Yang et al, 2009 ; Yang et al, 2013 ; Nourian et al, 2014 ). Decreased activity results in a smaller contribution of BK Ca channels to the cell membrane potential and this may in turn permit higher levels of vascular resistance in the skeletal muscle circulation ( Jackson & Blair, 1998 ; Hill et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%